On the Wiener-Laguerre transformation - Jürgen Glaeske, Hans (Rev. Téc. Fac. Ing. Univ. Zulia)
In this paper we investigate a discrete integral transformation on the real line, which, with respect to the convolution structure, is better adapted than the discrete Hermite transformation, introduced by Debnath. The kernels are complex-valued rational functions which are the Fourier transforms of the Laguerre polynomials and which were introduced by N. Wiener. Some remarks about a real version, following a paper of Christov are added.